2019
DOI: 10.1177/0018720819879313
|View full text |Cite
|
Sign up to set email alerts
|

Physical Exercise Intensity During Submersion Selectively Affects Executive Functions

Abstract: Objective: The intact cognitive processing capacity in highly demanding and dynamically changing situations (e.g., in extreme environmental conditions) is of central relevance for personal safety. This study therefore investigated whether underwater physical exercise (PE) affected cognitive performance by comparing these effects during underwater fin-swimming as opposed to inactivity under normal environmental conditions. Background: Although acute bouts of PE can modulate cognitive performance under highly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
4
12
2
Order By: Relevance
“…This work concentrates on investigating executive functions (EFs) that are considered cognitive processes, subserving higher goal-directing behavior (Friedman & Miyake, 2017). Tasks for EFs are easily comprehensible and offer a standardized and time-efficient way to investigate cognitive performance, even in extreme environments like underwater (Möller et al, 2021). EFs’ well-established model of unity and diversity describes response inhibition , switching, and updating as a pattern of shared but distinct functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work concentrates on investigating executive functions (EFs) that are considered cognitive processes, subserving higher goal-directing behavior (Friedman & Miyake, 2017). Tasks for EFs are easily comprehensible and offer a standardized and time-efficient way to investigate cognitive performance, even in extreme environments like underwater (Möller et al, 2021). EFs’ well-established model of unity and diversity describes response inhibition , switching, and updating as a pattern of shared but distinct functions.…”
Section: Introductionmentioning
confidence: 99%
“…We know from our recent study that fin-swimming exercise at 5 meters (m) water depth in a moderate exercise intensity of 20-min duration has a positive effect on inhibition (Möller et al, 2021). This confirms that shallow water immersion per se does not necessarily negatively impact EFs (Steinberg & Doppelmayr, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, we suggest that the fit2dive test also be used to perform scientific studies. These could further extent the knowledge on topics such as the relation between exercise intensity and cognitive competences [53] or on the effects of oxygen-enriched air on physiological variables (Zenske et al, 2019).…”
Section: Real Fin Swimmingmentioning
confidence: 99%
“…Moeller’s study has shown that exercise intensity can effectively affect the EF of individuals. In Moeller’s study, moderate-intensity physical exercise had a positive effect on inhibition control, while high-intensity physical exercise had no effect on inhibition control [ 16 ].…”
Section: Introductionmentioning
confidence: 99%